2023
DOI: 10.1128/spectrum.00309-23
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance Patterns and Molecular Characterization of Streptococcus suis Isolates from Swine and Humans in China

Abstract: S. suis is a serious zoonotic pathogen. In this study, we investigated the epidemiological and molecular characteristics of 96 S. suis isolates from 10 different provinces of China from 2008 to 2019.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 64 publications
(86 reference statements)
2
4
1
Order By: Relevance
“…Regarding quinolones, the resistance levels obtained were considered intermediate since the AMR values for ENRO and DANO were 49% and 60.9%, respectively. Notably, in all studies encompassing any of these antimicrobials [ 44 , 45 , 47 , 54 , 55 , 56 , 58 ] the resistance levels were considerably lower than those observed in this study. Specifically, the resistances detected were 2%, 9.6%, 1.4%, 11.1%, 2%, 11.5%, and 1%, respectively.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Regarding quinolones, the resistance levels obtained were considered intermediate since the AMR values for ENRO and DANO were 49% and 60.9%, respectively. Notably, in all studies encompassing any of these antimicrobials [ 44 , 45 , 47 , 54 , 55 , 56 , 58 ] the resistance levels were considerably lower than those observed in this study. Specifically, the resistances detected were 2%, 9.6%, 1.4%, 11.1%, 2%, 11.5%, and 1%, respectively.…”
Section: Discussioncontrasting
confidence: 80%
“…The resistance distribution for this antimicrobial mirrored that of the quinolones. Specifically, some of the AMR levels reported worldwide were 1.9% [ 59 ], 2% [ 56 ], 6.2% [ 45 ], 11.3% [ 54 ], and 19.8% [ 55 ]. Hence, it can be assumed that the AMR levels for this antimicrobial tend to be low.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly found combination of AMR genes was erm (B) –tet (O) carried by an IME/dIME inserted in SNF2 of an ICE of the Tn 5252 family ( n =41). This high frequency of erm (B) –tet (O) association has been extensively reported in S. suis [12, 16, 17, 45]. In addition to these AMR genes found on nested elements, 72 additional AMR genes were located on ICEs (seven of the vanG family, three of the Tn 916 family and one of the Tn 1549 family).…”
Section: Resultssupporting
confidence: 68%
“…In S. suis , antimicrobial resistance (AMR) is mainly conferred by acquired genes located on mobile genetic elements (MGEs), which are responsible for the dissemination between bacteria sharing the same environment [14–16]. Whole genome sequencing (WGS) combined with comparative genomic analyses was used to study AMR genes and their location on MGEs in S. suis strains isolated from various countries [12, 15, 17, 18]. These studies showed that two categories of MGEs called integrative conjugative elements (ICEs) and integrative mobilizable elements (IMEs) play an essential role in AMR dissemination in S. suis .…”
Section: Introductionmentioning
confidence: 99%
“…When an isolated bacterium demonstrates resistance to optochin, a simple and low-cost test for the presumptive identification of Streptococcus pneumoniae , the primary target of differential diagnosis, should be performed. Although conventionally, S. suis demonstrates a highly favorable and stable sensitivity profile, routine antimicrobial susceptibility testing is essential for monitoring the potential emergence of antimicrobial resistance 2 , 12 .…”
Section: Discussionmentioning
confidence: 99%